KEPATUHAN MINUM OBAT PADA ORANG DENGAN GANGGUAN JIWA MELALUI KUNJUNGAN RUMAH OLEH KADER KESEHATAN JIWA DI DENPASAR TIMUR - Sulistiowati, Ni Made Dian; Dewi, Ni Made Listya; Swedarma, Kadek Eka (Coping: Community of Publishing in Nursing; Vol 4 No 3 (2016): Desember 2016, 2016)
The recurrence rate of patients with mental disorder are still high and mostly caused by drug withdrawal. One strategy that can be done to overcome this is to do a home visit by a cadre of mental health. During a visit home, cadres to carry out the functions and role as the person who oversees the taking medication. This study aims to analyze the influence of home visits by a cadre of mental health on medication adherence People With Mental Disorder in the home. This study was a comparative study with quantitative approach. This study was quasi experiment with pre and post test design. There were 33 samples that collected by porposive sampling technique. The results of this study based on statistic test were obtained value of z = -3.873, with p value = 0,000, (p<? (0,05)). Based on the above findings, it can be concluded that there are significant impact of home visit on medication adherence People With Mental Disorder in the home. Keywords : cadre of mental health, home visits, medication adherence, people with mental disorders.